Research Pogress on Action Mechanism of NLRP3 Inflammasome and Pyroptosis in Diabetic Nephropathy - LEI Zhenyun; XUE Guozhong; LIU Zhenhua; ZHANG Xinli (Xiehe Yixue Zazhi)
Diabetic nephropathy (DN), as one of the most common complications of diabetes, is a primary cause of end-stage renal disease. The pathogenesis of DN encompasses processes such as chronic inflammation, recruitment and activation of immune cells, tubular and glomerular injury, and renal fibrosis. These processes are highly correlated with the activation of the nucleotide-binding oligomerization domain-like receptor pyrin domain containing 3 (NLRP3) inflammasome and the resulting pyroptosis it mediates. Previous studies have shown that the release of pro-inflammatory cytokines, leakage of damage-associated molecular patterns (DAMPs), recruitment and activation of immune cells can be reduced by regulating the NLRP3 inflammasome and its mediated pyroptosis, thereby slowing the diffusion of inflammatory responses in adjacentcells, fibrosis, and tissue remodeling processes. Ultimately, these process can improve renal injury and dysfunction caused by diabetic nephropathy. This article summarizes the molecular regulatory mechanisms of the NLRP3 inflammasome and its mediated pyroptosis at different pathological stages of DN, proposes potential targets for regulating their activation, aiming to provide a new direction for personalized treatment of DN.